Sinergi refleksi dan inovasi: arsitektur kecerdasan intrapersonal dalam desain matematika digital - Yenni; Raharjo , Sigit; Firmansyah, M. Arie (Universitas Muhammadiyah Prof. DR. HAMKA, 2025)
Purpose: This study describes how students with intrapersonal intelligence develop and implement mathematics lesson plans using interactive digital media, addressing instructional planning that often overlooks diverse intelligence profiles. Design/methodology/approach: Using a qualitative descriptive method, surveys first identified students' intelligence types. Structured observations then analyzed the alignment between students' intrapersonal traits and their activities during lesson plan implementation. Findings: Students with intrapersonal intelligence successfully designed digitally assisted learning plans using animated videos. Guided inquiry was their preferred method, actively accommodating intrapersonal traits like self-motivation, clear goal-setting, emotional management, and independent analytical thinking.Practical implications: Tailoring methods and media to specific intelligences helps educators and pre-service teachers create engaging lesson plans that boost student motivation and mathematics learning outcomes. Originality/value: This research uniquely maps the synergy between intrapersonal intelligence, guided inquiry, and digital media, offering new perspectives on personalized and differentiated mathematics instruction. Purpose: Studi ini mendeskripsikan bagaimana siswa dengan kecerdasan intrapersonal mengembangkan dan mengimplementasikan rencana pembelajaran matematika menggunakan media digital interaktif, membahas perencanaan pembelajaran yang sering mengabaikan beragam profil kecerdasan. Design/methodology/approach: Menggunakan metode deskriptif kualitatif, survei pertama-tama mengidentifikasi tipe kecerdasan siswa. Observasi terstruktur kemudian menganalisis keselarasan antara sifat intrapersonal siswa dan aktivitas mereka selama implementasi rencana pembelajaran. Findings:Siswa dengan kecerdasan intrapersonal berhasil merancang rencana pembelajaran yang dibantu secara digital menggunakan video animasi. Inkuiri terbimbing adalah metode pilihan mereka, secara aktif mengakomodasi sifat intrapersonal seperti motivasi diri, penetapan tujuan yang jelas, manajemen emosi, dan pemikiran analitis independen. Practical implications: Menyesuaikan metode dan media dengan kecerdasan spesifik membantu pendidik dan calon guru menciptakan rencana pembelajaran yang menarik yang meningkatkan motivasi siswa dan hasil belajar matematika. Originality/value: Penelitian ini secara unik memetakan sinergi antara kecerdasan intrapersonal, inkuiri terbimbing, dan media digital, menawarkan perspektif baru tentang pengajaran matematika yang dipersonalisasi dan terdiferensiasi.